The role of tumor-associated macrophages in HPV induced cervical cancer - Chen, Zeping; Zhao, Binzhu (Frontiers in Immunology, 2025)
Human papillomavirus (HPV), a double-stranded DNA virus linked to various malignancies, poses a significant global public health challenge. In cervical cancer, persistent infection with high-risk HPV genotypes, particularly HPV-16 and HPV-18, initiates immune evasion mechanisms within the tumor microenvironment. The polarization of tumor-associated macrophages (TAMs) from M1 to M2 phenotypes promotes cervical carcinogenesis, metastasis, and therapeutic resistance via establishing an immunosuppressive microenvironment. This review provides a comprehensive overview of HPV-induced immune evasion pathways, including MHC downregulation, T-cell impairment, regulatory T cell induction, and cGAS-STING pathway inhibition. Furthermore, describe the pivotal role of TAMs in cervical cancer progression, focusing on their phenotypic plasticity, pro-tumoral functions, and potential as therapeutic targets. By elucidating these cellular and molecular dynamics, this review aims to support advanced research. Targeting TAM polarization through immunotherapies and nanomedicine-based strategies represents a promising strategy for enhancing patient outcomes.